متطلبات تفعيل الاقتصاد الدائري في الجزائر - مسعودي، محمد Massoudi, Mohammed (جامعة الجزائر 3 - كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2020)
أصبح الاقتصاد الدائري في الوقت الراهن، محل اهتمام كبير من طرف العديد من الباحثين والمختصين في مجال حماية البيئة وتحقيق التنمية المستدامة، كما أن العديد من الدول - ومنها الجزائر- تسعى سعيا حثيثا لتجسيد مبادئه وأسسه على أرض الواقع، قصد تحقيق الكفاءة الاقتصادية في استغلالا الموارد الطاقوية والطبيعية من جهة، وحماية البيئة وضمان ديمومتها للأجيال المستقبلية من جهة أخرى. غير أنه اتضح لنا من خلال هذه الورقة البحثية، أن الاقتصاد الدائري في الجزائر، لا يزال يقتصر على جانب واحد فقط هو تسيير النفايات وإعادة تدويرها دونما الأخذ بعين الاعتبار للجوانب والأبعاد الأخرى للاقتصاد الدائري التي يتم تطبيقها في العديد من الدول المتقدمة؛ وهو ما يستدعي تبني إجراءات وميكانيزمات مستقبلية من تفعيل الاقتصاد الدائري أكثر فأكثر في الجزائر.
Now, the circular economy has become a major concern of many researchers and specialists in the field of environmental protection and sustainable development. In addition, many countries, including Algeria, are actively seeking to embody its principles and foundations on the ground, in order to achieve economic efficiency in the exploitation of energy and natural resources on the one hand, and to protect the environment and ensure its sustainability for future generations on the other. However, it is clear from this paper that the circular economy in Algeria is still limited to only one aspect: waste management and recycling without taking into account the other aspects and dimensions of the circular economy that are applied in many developed countries. And This calls for the adoption of future procedures and mechanisms that will enable the activation of the circular economy in Algeria more and more.
Keywords: التنمية الاقتصادية -- المنظومة الإنتاجية -- الموارد الطبيعية -- حماية البيئة -- الجزائر